2008
DOI: 10.1002/eqe.797
|View full text |Cite
|
Sign up to set email alerts
|

Performance of seismic‐isolated bridges with and without elastic‐gap devices in near‐fault zones

Abstract: SUMMARYIn this paper, the efficiency of providing elastic-gap devices (EGDs) to improve the performance of seismic-isolated bridges (SIBs) in near-fault (NF) zones is investigated. The device is primarily made of an assembly of circular rubber bearings and steel plates to provide additional elastic stiffness to the SIB upon closure of a gap. The EDG is intended to function at two performance levels under service and maximum considered design level (MCDL) NF earthquakes to reduce isolator displacements while ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For structures subjected to earthquakes with intense long duration acceleration pulses, although seismic isolation technology may be used to reduce and control the magnitude of the forces, such a system alone may not be adequate to reduce the displacement demand to practical ranges of application [1]. In such cases, a combination of seismic isolation and dampers is used to reduce and control both forces and displacements.…”
Section: Introductionmentioning
confidence: 99%
“…For structures subjected to earthquakes with intense long duration acceleration pulses, although seismic isolation technology may be used to reduce and control the magnitude of the forces, such a system alone may not be adequate to reduce the displacement demand to practical ranges of application [1]. In such cases, a combination of seismic isolation and dampers is used to reduce and control both forces and displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Large pulses and permanent displacements are characteristic for near‐fault ground motion and as such, strong shaking close to earthquake sources can be completely different from far‐field motions. It has been shown that when an earthquake fault is near, structural responses are noticeably affected by the amplitude and period of the velocity pulses 33–38 . It has also been shown that consideration of the ground‐motion vertical component in the design of highway bridges, particularly those near faults, is important 39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Collision shear walls have been found to be effective in reducing the consequences of pounding (Anagnostopoulos and Karamaneas, [5]). Elastic gap devices (see, for example, Dicleli, [6]), have been shown to be effective in mitigating damage caused by pounding.…”
Section: Introductionmentioning
confidence: 99%